The Effect of Workload, Distributive Injustice and Job Burnout on Employee Performance with Quiet Quitting as an Intervening Variable in Employees at Public Works and Highways Department of East Java Province - Ario Bagus Nugroho; Siti Mujanah; I Dewa Ketut Raka Ardiana (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2025)
Human Resource Management has many functions like organizing on how to determine the workload of every employee, controlling their employee’s workload, providing fair and appropriate compensation also integrating the employee’s needs and the organization’s expectation of them. Every workplace which has employees detached, losing motivation and initiative while working because of the workload, tiredness or the feeling of injustice, would most likely disturb their employee performance. This study aimed to test and analyze the effect of workload, distributive injustice and job burnout also analyzed and test the role of quiet quitting on every path of the relationship between these variables on employee performance. This Study used quantitative approach, and questionnaire was distributed via online form to 100 employees of Public Works and Highways Department of East Java Province. Hypothesis testing was carried out by using SEM-PLS algorithm through the Smart-PLS 4 Application. The results of this study indicate that workload, job burnout, and quiet quitting significantly affect employee performance, while distributive injustice does not. Additionally, job burnout significantly influences quiet quitting, whereas workload and distributive injustice do not. As an intervening variable, quiet quitting mediates the relationship between distributive injustice and employee performance, as well as job burnout and employee performance, but not workload and employee performance.